2021
DOI: 10.13057/biodiv/d220263
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Molecular study on mt-DNA COX2 gene of Sumatran elephant (Elephas maximus sumatranus)

Abstract: Abstract. Wibowo DS, Widiyanti R, Asvan M, Restanti PD, Wijayanto H. 2021. Short Communication: Molecular study on mt-DNA COX2 gene of Sumatran elephant (Elephas maximus sumatranus). Biodiversitas 22: 1063-1068. Sumatran elephant is the only subspecies of Asian elephants that receives a critically endangered status from the International Union for Conservation and Nature Resources (IUCN). Identifying the genetic marker of Sumatran elephants is, therefore, important for their conservation. This study aimed to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(18 reference statements)
1
2
0
Order By: Relevance
“…This high similarity also suggested that mtDNA diversity, especially in the Cytochrome b gene region, is very low in the Seblat. This result is in agreement with previous studies using other mtDNA fragments, such as D-loop, COXII, and COI (Sulandari & Zein, 2012;Wibowo et al, 2021;Virnarenata et al, 2021). The low genetic diversity of Sumatran Island may also increase higher reproductive failure because removal of heterozygous alleles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This high similarity also suggested that mtDNA diversity, especially in the Cytochrome b gene region, is very low in the Seblat. This result is in agreement with previous studies using other mtDNA fragments, such as D-loop, COXII, and COI (Sulandari & Zein, 2012;Wibowo et al, 2021;Virnarenata et al, 2021). The low genetic diversity of Sumatran Island may also increase higher reproductive failure because removal of heterozygous alleles.…”
Section: Discussionsupporting
confidence: 93%
“…A previous study reported by Sulandari and Zein (2012) described that low haplotype and nucleotide diversities were found in Sumatran elephant populations based on the D-loop region of mtDNA. The low genetic diversity of the Sumatran elephant originating from the South Sumatera area is also reported by Wibowo et al (2021) using mtDNA Cytochrome Oxidase subunit II (COX2). Moreover, Virnarenata et al (2021) reported that a close genetic relationship was found in the Sumatran elephant conserved in Way Kambas National Park based on mtDNA Cytochrome Oxidase subunit I (COI).…”
Section: Introductionmentioning
confidence: 72%
“…Asian elephant is widely distributed in South Asia, especially in Peninsular Malaysia, Sumatra, and Kalimantan (Borneo) (Wibowo et al 2021). Sumatran elephant is one of Asian elephant subspecies labelled Critically Endangered (CE) by International Union for Conservation of Nature (IUCN).…”
Section: Introductionmentioning
confidence: 99%